The Performance Impact of New Ventures in Working Environment and Innovation Behavior From the Perspective of Personality Psychology - Yang, Shufang; Wu, Hainan (Frontiers in Psychology, 2021)
A new venture barely makes a profit in its initial stage, and its success depends on innovation. Innovation is related to the work environment, and the innovation behavior of employees is of great significance to the performance improvement of new venture. Based on the previous research, in this study, hypotheses on the correlation between work environment, employee innovation behavior, and corporate performance are put forward first. Then, with team cooperation, organizational incentive, leadership support, sufficient resources, and work pressure as the factors of the work environment, the bosses, middle and senior managers involved in entrepreneurship, and the main members of the entrepreneurial team of 202 newly established enterprises in developed regions are surveyed online or in scene. Multivariate hierarchical regression analysis is performed to analyze the data collected from the questionnaire. The results show that the effective recovery rate of the questionnaire is 86.4%; the number of traditional enterprises is 108 (53.47%), and that of R&D enterprises is 68 (33.66%); teamwork, leadership support, and work pressure are all correlated with employees' innovative behavior (P<0.05), while organizational motivation and sufficient resources are not correlated with employees' innovative behavior (P>0.05); employee innovation behavior is positively correlated with enterprise performance (β=0.375, P≤0.01); the working environment and employee innovation behavior promote enterprise performance (β=0.433, P≤0.01); and the working environment affects the relationship between employee innovation behavior and enterprise performance (β=0.399, P≤0.05). The study theoretically enriches the research on the relationship between innovation behavior, work environment, and enterprise performance of new ventures. In practice, it is suggested that start-up enterprises provide good working environment for employees and attach importance to innovation activities at the individual level of employees, which provides useful guidance and reference for the development of Chinese start-up enterprises.